2016
DOI: 10.1007/s00436-016-5297-6
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of five parasitic pathogens in pregnant women in ten Caribbean countries

Abstract: To date, published epidemiological studies of parasitic infections in humans in the Caribbean region are very limited. Here, we report the seroprevalence of five parasitic pathogens, including Ascaris lumbricoides, Entamoeba histolytica, Giardia lamblia, Schistosoma mansoni, and Toxocara canis in 435 serum samples collected between 2008 and 2011 from pregnant women in ten Caribbean islands. We tested the serum samples for IgG antibodies against the five parasites by enzyme-linked immunosorbent assay (ELISA). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…After malaria, amoebiasis is the second cause of death due to parasitic diseases [4,5]. The symptoms vary from mild diarrhea to dysentery, but, occasionally, E. histolytica can invade the intestinal mucosal barrier and trigger liver abscesses [6]. Asymptomatic infections occur in 90% of individuals, whereas the remaining 10% contract symptomatic infections [7].…”
Section: Introductionmentioning
confidence: 99%
“…After malaria, amoebiasis is the second cause of death due to parasitic diseases [4,5]. The symptoms vary from mild diarrhea to dysentery, but, occasionally, E. histolytica can invade the intestinal mucosal barrier and trigger liver abscesses [6]. Asymptomatic infections occur in 90% of individuals, whereas the remaining 10% contract symptomatic infections [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found varying seroprevalences of Giardia and Cryptosporidium . In the Caribbean, 41% of pregnant women were found to be seropositive for Giardia [32]. A national survey in Mexico showed a Giardia seroprevalence of 55% [33].…”
Section: Discussionmentioning
confidence: 99%
“…Among protozoa, Giardia intestinalis (syn. G. lamblia – G. duodenalis ) is the most common species, with an estimated 1.2–2 million cases per year and infection rates from 0.4 to 7.6% in developed countries and from 0.9 to 40% in LMIC [ 3 ]. Although they are rarely the direct cause of death, IPIs can induce malabsorption, diarrhea, blood loss, anemia, reduced work capacity, and reduced growth, thus representing important health and social problems.…”
Section: Intestinal Parasitic Infectionsmentioning
confidence: 99%